EU Protection Policy on Solar Panel Imports from China in 2013 - Madaniyah (Pt. Anagata Sembagi Education, 2024)
This study seeks to elucidate the rationale behind the European Union's adoption of an anti-dumping measure concerning the importation of Chinese solar panels in 2013. Employing a qualitative explanatory approach grounded in the concept of protectionism, the research delves into the European Union's strategic considerations. Given the region's reliance on fossil fuel imports, there exists a pronounced emphasis on renewable energy sectors, particularly solar panels. Initially a frontrunner in solar panel production, the European Union has encountered increasing competition from China. In response to this intensified competition within the solar panel industry, the European Union opted for a protectionist stance, manifested in the form of anti-dumping measures aimed at addressing the significantly lower selling prices of Chinese products, which fell below established minimum thresholds.